Metalanguage for Spoken Discourse in Reading to Learn (R2L) (2024)
Reading to learn (R2L) is an instructional approach in which teachers support learners in the creation of meaning in texts. To that end, the approach follows a 3-stage cycle that moves learners from joint to independent creation of meaning to fulfill a purpose socially through language. To date, few studies have explored the role of metalanguage as a tool to support learners during each stage of the R2L cycle (for oral communication. Therefore, this case study aimed to find out how SFL metalanguage could serve as an aid during students’ creation of spoken texts throughout R2L instruction. Under the scope of Systemic Functional Linguistics (SFL), metalanguage refers to the language used for talking about language itself, used to identify and explain meaning in contexts. This study was part of a larger investigation that sought to explore a teacher’s changes in praxis as she learned R2L for spoken discourse in a state high school in Cordoba, Colombia. Analysis of Metalinguistic literacy events (MLE) presented during observations and learning sessions revealed that the teacher first learned the metalanguage needed for the chosen genre and later included it during her class development for different purposes such as explaining the genre, guiding the activity, and helping students to achieve the lesson goals. Furthermore, students used metalanguage to identify the stages and create meaningful and purposeful spoken texts. This study contributes to the existing body of knowledge as well as invites further exploration and refinement of metalanguage integration within educational practices in the language classroom.